Particulated Juvenile Articular Cartilage Implantation in the Knee: A 3-Year EPIC-µCT and Histological Examination. (April 2014) - Stevens, Hazel Y.; Shockley, Blake E.; Willett, Nick J.; Lin, Angela S.P.; Raji, Yazdan; Guldberg, Robert E.; Labib, Sameh A.
Objective: The goal of this report is to describe the outcome of sequential particulated cartilage allograft and autologous osteochondral transfer treatments for an osteochondral lesion of the medial femoral condyle. Methods : A 44-year-old woman was treated with a particulated juvenile articular cartilage allograft ( DeNovo NT) for a chondral lesion of the knee. As a result of continued pain, she had 2 further surgeries, including an autologous osteochondral transfer system procedure and finally a unicondylar knee arthroplasty. At the final procedure, the areas of the allograft and autograft tissue were biopsied for histological evaluation. The quality of the residual cartilage tissue was assessed first by equilibrium partitioning of an ionic contrast agent via micro–computed tomography (EPIC-µCT), and then by hematoxylin and eosin, Safranin O staining, and polarized light microscopy. Results : Despite showing good healing at 7 months postsurgery by MRI, at 28 months post DeNovo NT tissue implantation the excised cartilage tissue was heterogeneous, with some regions of hyaline-like cartilage and some regions of fibrocartilage. The later mosaicplasty may have helped maintain hyaline-like cartilage of the DeNovo NT tissue in its vicinity. Conclusion : This case report describes the cartilage repair tissue produced by DeNovo NT implantation and compares it with autologous osteochondral plug tissue.